Factors influencing the adoption of the Crowdfunding-Waqf Model (cwm) in the waqf land development - Mohd Thas Thaker, Mohamed Asmy (Emerald Group Publishing Ltd., 2018)
Purpose – This study is designed to examine the behavioural intention of donors or crowd funders to use Crowdfunding Waqf Model (CWM), as this model is proposed to address the liquidity problem faced by Waqf institution in Malaysia Design/methodology/approach – The primary data are collected from the survey administered to donors or crowd funders in Klang Valley and the analysis is conducted using Partial Least Squares (PLS). The model has validated its acceptance in the field by adopting the theory of Technology Acceptance Model (TAM). Findings – This study has revealed that both the perceived usefulness and perceived easy to use are found to have a positive impact on the intention of donors or crowd funders in assisting Waqf institution to develop Waqf land in Malaysia. Furthermore, perceived easy to use has a positive relationship and direct effect with perceived usefulness of crowd funders to use the Crowdfunding Waqf Model Research limitations/implications – The variables that have been used based on TAM in this study are constantly in flux. There are other variables such as trust, social norm, orientations that might be affecting the adoption level of donors or crowd funders in Malaysia. In addition, the current study is covering only Klang Valley, Malaysia. Future research is nevertheless still required that incorporate other variables and extend the study to other states of Malaysia. Practical implications –The findings of this paper will provide Waqf institution with an alternative source for raising capital to develop Waqf asset. The present study also has implications for government and policy makers. Originality/value – To the best of the author’s knowledge, no study has incorporated an element of crowdfunding to develop Waqf land. Thus, the present study is relevant in extending the importance of crowdfunding as a source of financing for Waqf institutions in developing Waqf land